Integrasi Teknologi Digital dalam Pembelajaran Berdiferensiasi di Sekolah: Tinjauan Naratif Teori dan Praktik - Fahmi Yahya; N Nurhairunnisah; Hermansyah Hermansyah; Suharli Suharli (Indonesian Journal of Teacher Education, 2021)
The diversity of students in terms of learning readiness, interests, and learning profiles demands a learning approach that accommodates individual differences, one of which is through differentiated learning. The widespread development of digital technology after the pandemic and in line with the agenda for digital transformation in education opens up opportunities to realize differentiation more practically and at scale. This article is a narrative review that synthesizes the theoretical foundations and practical evidence of digital technology integration in differentiated learning based on the literature from 2018–2021. The study shows that digital technology plays a role as an enabler of differentiation in content, processes, products, and learning environments through adaptive and personalized learning, multimodal resources, flipped and blended learning models, and data-driven formative assessment. However, this integration does not occur automatically. Its effectiveness depends on the quality of pedagogical design, teachers' technological-pedagogical competencies (TPACK), and equitable access. The digital divide, diverse conceptualizations of differentiation, and the risk of technology dominating pedagogy are key challenges. This article recommends strengthening teacher competencies and learning designs based on the principles of differentiation as the key to meaningful integration.